A novel animal model for subcutaneous soft tissue infection - Zulaziz, Natasha; N. , Himeno; H. , Miyazaki; D. , Saitoh; Noor Azmi, Azran Azhim; Y. , Morimoto (J-STAGE, 2014)
In order to simultaneously monitor neutrophil migration in vivo during inflammation, we developed a novel animal model for subcutaneous soft tissue infection using transgenic mouse bearing fluorescence-positive neutrophils and bioluminescent methicillin-resistant Staphylococcus aureus (MRSA). Methods: Eight to nine-week-old male lys-EGFP C57BL/6 were anesthetized (50 mg/kg pentobarbital sodium, ip) and 1.0 ×107 CFU of bioluminescent MRSA (Xen31, PerkinElmer) were subcutaneously injected. Control group was injected with PBS while the treatment group was given Arbekacin (25 mg/kg) intravenously via tail vein. For the evaluation of MRSA activity and neutrophil accumulation, an in vivo imaging system (LAS-4000, GE) was performed. Results: Both groups displayed similar pattern with significant drop in MRSA bioluminescence and neutrophil fluorescence peaked on day 1. However, bacterial infection completely resolved in treatment group by day 6 with gradual decline in neutrophil fluorescence. Conclusions: This animal model could be a competent method for assessment of subcutaneous soft tissue infections.